Light aerobic exercise modulates executive function and cortical excitability. (1st November 2019) - Morris, Timothy P.; Fried, Peter J.; Macone, Joanna; Stillman, Alexandra; Gomes‐Osman, Joyce; Costa‐Miserachs, David; Tormos Muñoz, Jose Maria; Santarnecchi, Emiliano; Pascual‐Leone, Alvaro
Abstract: Single bouts of aerobic exercise can modulate cortical excitability and executive cognitive function, but less is known about the effect of light‐intensity exercise, an intensity of exercise more achievable for certain clinical populations. Fourteen healthy adults (aged 22 to 30) completed the following study procedures twice (≥7 days apart) before and after 30 min of either light aerobic exercise (cycling) or seated rest: neurocognitive battery (multitasking performance, inhibitory control and spatial working memory), paired‐pulse TMS measures of cortical excitability. Significant improvements in response times during multitasking performance and increases in intracortical facilitation (ICF) were seen following light aerobic exercise. Light aerobic exercise can modulate cortical excitability and some executive function tasks. Populations with deficits in multitasking ability may benefit from this intervention. Abstract : Light intensity aerobic exercise, suited to populations who may be unable to exercise at higher intensities can modulate multitasking performance and cortical excitability in a facilitative direction. Consistent with previous research, however, this intensity of exercise does not appear to modulate widespread executive functions.